Experimental Legislation in China between Efficiency and Legality The Delegated Legislative Power of the Shenzhen Special Economic Zone - Martinek, Madeleine (Springer International Publishing, 2018)
This book analyzes the benefits of and legal concerns in connection with the delegated legislation of the Shenzhen Special Economic Zone as a prime example of experimental legislation in Chinese law. It offers solutions for improving the legal design of experimental regulations in Special Economic Zones by striking a balance between the pursuit of rapid socio-economic progress on the one hand, and the increasing need and will to govern by the rule of law on the other. The book offers a valuable guide for the academic community and legal practitioners, as well as students eager to gain insights into Chinese constitutional law and the conflict between legality and achieving reforms.